Working Conditions, Transparency, and Compliance in Global Value Chains: Evidence from Better Work Jordan - Raymond Robertson (Institute of Labor Economics (IZA), 2019)
This paper estimates how compliance with national labor law and international labor standards within Jordan's garment exporting factories changed after the implementation of a transparency program that made compliance assessments publicly available. The estimation employs data from Better Work Jordan that cover all garment-exporting factories over the 2008-2018 period. Using a difference-in-difference approach that is often applied to control for endogeneity, this paper finds that compliance improved following the implementation of transparency. Compliance increased in a group of 28 critical compliance areas that represent fundamental worker rights relative to relevant comparison groups. The results are robust to a number of additional controls, definitions of the transparency period, and estimation approaches.
Keywords: J8; J5; J3; 330; global value chains; working conditions; transparency